Kecintaan Pada Uang dan Persepsi Anti Korupsi - Nizma Triana; Adi Heryadi (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
The purpose of this study was to study the relationship between the attitude of love of money (perception of money) with the perception of anti-corruption in regional bureaucratic employees in Sleman Regency. This study uses quantitative methods that are analyzed using statistical analysis of product moment evaluations from Carl Pearson. The sample used in this study was obtained using saturated sampling technique. The sample of this research is the staff of the Sleman Regency Regional Finance and Asset Agency which gathers 77 employees. The research data was collected through a scale of love money attitude with a value (α ) of 0.979 and an anticorruption perception scale with a value (α ) of 0.960. Statistical test results obtained with a positive correlation coefficient of 0.514, with a significance level of 0.000 (p <0.05), this shows a significant positive relationship between the attitude of love of money with the perception of anti-corruption. Successful, the higher the attitude of love for money, the higher the perception of anti-corruption needed by employees and vice versa, the lower the attitude of love of money, the lower the perception of anti-corruption that demands employees. The average subject has an attitude of love for money and perceptions of anti-corruption in the medium category. The effective contribution of the love attitude of money to the perception of anti-corruption amounted to 26.4% and 73.6% of the perception of anti-corruption by other factors in the study.